TRANSMISSION AND HOST RANGE DETERMINATION OF DOLICHOS MOSAIC VIRUS OF FIELD BEAN (LABLAB PURPUREUS L.) - H. M. RENUKA; H. K. RAMAPPA; B. S. PAVITHRA (The Bioscan, 2015)
A preliminary work on Transmission and Host range determination of DMV was conducted. Dolichos mosaic virus (DMV) disease of field bean caused by a poty virus and it was readily sap transmissible. The percentage of sap transmission varied from 88.00 to 93.08. The symptoms like vein clearing, uneven leaf lamina, mosaic mottling, blistering, puckering of leaves appeared on test plants 8 -10 days after inoculation. The virus was transmissible by the two species of aphid viz., Myzus persicae Sulz. and Aphis craccivora Koch. to a maximum of 72.00 and 33.34 per cent respectively. The Myzus persicae Sulz was more efficient vector. The virus was to be seed transmissible. The level of seed transmission of the virus varied from 5.80 to 12.06 per cent, with an average of 10.30 per cent. The virus produced systemic symptoms on Glycine max L. Phaseolus lunatus L. Phaseolus vulgaris L. and Vigna umbellata. The DMV was transmitted through sap, Aphid and Seed and produced systemic symptoms on above three host plants.